Morphological alterations caused by manual venom extraction on the main venom gland of Bothrops asper and Crotalus simus snakes (Serpentes: Viperidae): Long-term implications for antivenom production - Rodríguez Abarca, Sylvia; Universidad Nacional (Costa Rica). Escuela de Ciencias Biológicas. Licenciatura en Biología (Heredia, Costa Rica : S. Rodríguez A., 2019)
The only scientifically validated treatment for snakebite envenomation is the administration of antivenoms. For their production, small quantities of snake venom are injected in animals to elicit a specific antibody response. Snakes are kept in captivity, and their venom is regularly extracted to assure antivenom access. It has already been reported that the pressure exerted upon the venom gland during this extraction can cause tissue damage and fibrosis, leading to a decrease in the venom yield. We described the histopathology of venom glands for B. asper and C. simus snakes used for antivenom production. Based on these reported tissue abnormalities, we quantify the tissue injury by a generated damage-SCORE and fibrosis. A variety of histopathological damages were found such as fibrosis, edema, necrosis, hemorrhage, and formation of anomalous structures, especially in C. simus, which is more prone to suffer severe damage. The level and severity of the damage depend on the frequency and the number of venom extractions. Furthermore, we design an experimental intensive venom extraction scheme with which we could confirm the causality of these effects. In addition to the histopathological damages, the LD50 and biochemical venom composition were also affected giving experimental evidence that the venom extraction not only causes tissue damage but also affects the composition stability and toxicity of the venom. In order to produce quality and effective antivenoms, an improvement of the management of snake collections could be established, such as rotation groups to assure the quality of the venom yielded.
CD contiente únicamente el artículo y acceso DOI para consultar el documento de forma completa
Énfasis en Manejo de Recursos Naturales
Modo de acceso: vía internet
Modalidad de graduación : Artículo científico.
Tesis (Licenciatura) -- Universidad Nacional, Heredia, 2019
Keywords: SERPIENTE; VENENOS DE SERPIENTES; ENFERMEDADES DE LOS ANIMALES; MORFOLOGÍA (ZOOLOGÍA)